Health risk assessment of lead and cadmium in milk-based products of Iran - Zohre Farahmandkia; Behrouz Tajdar-oranj; Leila Zare; Mazyar Peyda; Rezgar Feizolahi; Adel Mirza Alizadeh (Journal of Agriculture and Food Research)
The primary objective of this study is to assess the health risks associated with lead (Pb) and cadmium (Cd) contamination in dairy products consumed in Iran. To conduct the research, 132 samples of cow milk, yogurt, cream, and doogh (a traditional Iranian beverage) were collected from both traditional and industrial livestock farms in Zanjan, Iran. The samples were microwave-digested, and an atomic absorption spectrophotometer equipped with a graphite furnace was used to determine toxic metals contents. The findings of the study revealed that the average concentrations of Pb in milk and dairy product exceeded the permitted limits. The mean ± se levels of Pb and Cd in milk, yogurt, doogh, and cream were 92.64 ± 8.73, 52.19 ± 8.42, 78.80 ± 12.89, 106.07 ± 8.94 μg/kg and 2.34 ± 0.22, 1.21 ± 0.20, 2.59 ± 0.57, 5.61 ± 0.63 μg/kg, respectively. For the purpose of exposure assessment, the chronic daily intake (CDI) was utilized, while the Hazard Quotient (HQ) and Total Hazard Quotient (THQ) were employed for non-carcinogenic risk assessment. Additionally, the Incremental Lifetime Cancer Risk (ILCR) was utilized for carcinogenic risk assessment. The results revealed that the highest exposure to Pb and Cd in the P 95th of CDI were observed in milk, followed by yogurt, doogh, and cream. According to our finding, the HQ and THQ values for potentially toxic elements (PTEs) related to the consumption of dairy products in the P 95th of cumulative probability were below 1. The results indicate that the ILCR of Cd (P 95th) due to the consumption of dairy products falls within the acceptable risk range (10−4 to 10−6). While our findings indicate levels of Cd in dairy products, it is important to note that there are currently no established standards for permissible Cd concentrations in Iran. Therefore, further research and regulatory frameworks are needed to ensure public safety.